Mikroorganisme Patogen Penyebab Foodborne Disease dan Gejalanya terhadap Kesehatan Tubuh di Masyarakat (Studi pada Masyarakat di Kecamatan Cigugur Tengah) - Essy Zulfiani; Mona Meilani (MASALIQ, 2025)
This study is motivated by the high incidence of foodborne diseases, which are infectious and toxic illnesses caused by pathogens entering the body through food. Food serves as an easy medium for disease transmission because it can carry pathogenic microorganisms to parts of the body vulnerable to infection. The research aims to identify pathogenic microorganisms causing foodborne diseases and the symptoms they produce in the community of Cigugur Tengah District. A mixed methods approach was used, combining field studies through observation, interviews, and documentation with literature review from various scientific publications. The findings indicate that foodborne diseases can be caused by infection from microorganisms such as bacteria, fungi, viruses, and parasites, as well as by intoxication. The pathogenic microorganisms identified include Salmonella spp., Clostridium spp., Campylobacter spp., Escherichia coli, Listeria monocytogenes, Yersinia spp., Toxoplasma gondii, and others. Common symptoms experienced by the community include diarrhea, nausea, vomiting, fever, and digestive disorders. The study also reveals that low public awareness of food sanitation and unhygienic food processing practices are dominant factors in the spread of this disease. This research contributes to raising public awareness and formulating more targeted health policies, particularly in food safety and the prevention of foodborne diseases.